Faktor-Faktor yang Mempengaruhi Penerapan Cara Produksi yang Baik dan Standar Prosedur Operasi Sanitasi Pengolahan Fillet Ikan di Jawa - Budi Yuwono; Fransiska Rungkat Zakaria; Nurmala Katrina Pandjaitan (Institut Pertanian Bogor, 2012)
In order to increase quality and safety of fish fillet products, Directorate General of Fisheries Product Processing and Marketing, Ministry of Marine Affairs and Fisheries, introduced Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) of fish fillet to the industry in Indonesia, including in Java. Recently, some processor who already applied GMP and SSOP do not continue the application of GMP and SSOP. Due this situation, this report is to find all factors that influence continuity application of GMP and SSOP processes of fish fillet and to see the recent condition of application of GMP and SSOP in fillet processing plants which do not continue (BM). Processing and analyzing the data using description method and pre-requisite analysis. The respondents of this research are 26 fish fillet processing plants in Java which are divided into 15 fish fillet processing plants that do not continue the application of GMP and SSOP (BM) and 11 fish fillet processing plants that are still continuing the application (LM). The factors that influence continuity application of GMP and SSOP in fish fillet processing plants that do not continue the application (BM) can be divided into internal factors which are lack of education (73%), and lack of experience (100%), external factors which are lack of government policies in socialization (66,66%), lack of portable water (87%) and ice supply (67%), lack of cold chain system facility (74%), lack of government policies in training (60%), monitoring (80%), lack of low enforcement (86%), no market requirement (100%), and characteristic of innovation factors which are no relative advantages in implementing GMP and SSOP (86,67%), no compatibility (80%), and the complexity of GMP and SSOP (73,33%). Base on pre requisite analysis, the status of GMP and SSOP in 15 fish fillet processing plants that do not continue (BM) the application is very bad as shown in high minor and mayor failure, and also serious and critical failure more than tolerance level. In order to support the application of GMP and SSOP in 15 fish fillet processing plants that do not continue the application (BM), it is suggested to increase the frequency of socialization, training, monitoring and technical counseling in special locus, facilitating water and ice supply, enforce the GMP and SSOP label in fisheries products in domestic market, and increasing education regarding the importance of GMP and SSOP application in fish fillet industry to the public